The UN's role in nation-building : from the Congo to Iraq - Dobbins, James, 1942- (Rand Corporation monograph series (Online), 2005)
Reviews UN efforts to transform eight unstable countries into democratic, peaceful, and prosperous partners, and compares those missions with United States nation-building operations. The UN provides the most suitable institutional framework for nation-building missions that require fewer than 20,000 men -- one with a comparatively low cost structure, a comparatively high success rate, and the greatest degree of international legitimacy.